Ritual e cosmologia Maxakali: uma etnografia sobre a relação entre os espíritos-gaviões e os humanos - Douglas Ferreira Gadelha Campelo (2009)
In this paper, I analyze the relation established between the Tikmn (Self-denomination of the Maxacali indian group, located at the northeast region of the state of Minas Gerais) and those dwelling spirits of their cosmos known as mõgmõxop (hawks). With the aim for understanding how this relation works, it was made ethnography of these spirits passing through Maxakali lands, as well as a study on the works previously elaborated concerning the tikmn kinship system and, at last, a study related to a group of myths narrated by the Tikmn. Through observation and analysis of the chants sung by the Hawk spirits, their movements, the interaction between the Hawk spirits and human beings, we looked for gaps, traces and elements in order for us to make inferences on this sort of relation. Considering some chants intoned by the Hawk-spirits, it could also be perceived the use of several kinship terms. Through the study of the Maxacali kinship terminology, it was possible to presume which is the Hawks point-of-view in this kinship system and the terms that guide the relation between the Hawk-spirits and the tikmn. Moreover, through the analysis of a myths group, it was intended to see the particularity of the relation between the Tikmn and the Hawk spirits, in comparison with the relation of the Tikmn with other spirits.